Improving Community Economy Through Innovation in Soft Ice Cream Machine and Food Dehydrator Technology and the Development of Local Wisdom in Sambibulu Village - Marwiyah, Siti; Hartati, Fadjar Kurnia; Suryawati, Cicilia Tantri; Tampubolon, Liosten Rianna Roosida Ully; Kurniawati, Ony (Unram Journal of Community Service, 2025)
Empowering Assisted Villages with the title "Improving Community Economy through Innovation in Soft Ice Cream Machine and Food Dehydrator Technology and Developing Local Wisdom in Sambibulu Village." The goal of the Mentored Village Program is to increase income, quality, and production capacity so that the target partner products can be competitive in the market. The problems faced by target partners 1 and 2 are that the types of products are still limited, namely: red guava, crystal guava, duck water tourism, cafes, and children's swimming pools. The solution to solve the partners' problems is the implementation of innovative ice cream machine technology, food dehydrator machines, and skills development to cultivate a local wisdom-based culture. The methods used to implement the proposed solutions are through training, mentoring, and practical operation and maintenance of innovative machine technologies and local wisdom culture. The target GDP achievement shows an increase in income for the target partner 2 of Rp. 6,000,000 per month for the ice cream business, an increase in income for target partner 1 of Rp. 7,000,000 per month for the flour, juice, and red guava chips business, and an increase in 3 types of product diversification. The external outputs of GDP are articles in Sinta 4 community service journals, videos, publications in mass media, posters, and the Unitomo YouTube channel.